1990
DOI: 10.1159/000195871
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Effects on Rheology and Clearance of Bronchial Mucus after Short-Term Administration of High Doses of Carbocysteine-Lysine to Patients with Chronic Bronchitis

Abstract: The rheological behavior and clearance of bronchial mucus samples collected by protected expectoration from 24 out-patients with simple chronic bronchitis were investigated before, at the end of a short period of treatment (4 days) with a single oral dose of 2.7 g (sachet) of carbocysteine-lysine (evening meal), and on the 4th and 8th days after the end of treatment versus placebo. In the group treated with carbocysteine-lysine, there were significant reductions in viscosity (-67, -48, -62%) and increases in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 3 publications
0
22
0
4
Order By: Relevance
“…Th is drug is a mucolytic agent available in Europe and Asia that has been demonstrated to reduce sputum viscosity and increase mucociliary transport. 250 Only three studies 251 -253 were deemed to be of suffi cient quality to be included, but a pooled analysis could not be performed because of the heterogeneous nature of the studies. S-CMC-lys was given to patients in a multicenter randomized placebo-controlled trial performed in 662 outpatients with chronic obstructive bronchitis.…”
Section: Underlying Values and Preferencesmentioning
confidence: 99%
“…Th is drug is a mucolytic agent available in Europe and Asia that has been demonstrated to reduce sputum viscosity and increase mucociliary transport. 250 Only three studies 251 -253 were deemed to be of suffi cient quality to be included, but a pooled analysis could not be performed because of the heterogeneous nature of the studies. S-CMC-lys was given to patients in a multicenter randomized placebo-controlled trial performed in 662 outpatients with chronic obstructive bronchitis.…”
Section: Underlying Values and Preferencesmentioning
confidence: 99%
“…There were signifi cant reductions in both sputum characteristics with carbocisteine in patients with initial sputum viscosity and elasticity above the mean value previously established in similar patient groups. There is also in vivo and in vitro evidence of increased mucociliary clearance velocity with carbocisteine, particularly in patients with slow clearance before treatment (Kohler et al 1982;Braga et al 1990). This, apparently selective, action supports a mucoregulatory mechanism and, in clinical practice, supports the careful selection of patients for treatment with carbocisteine when it is prescribed for a possible symptomatic benefi t associated with enhanced sputum clearance.…”
Section: In Vitro Ex Vivo and In Vivo Properties Of Carbocisteine Mumentioning
confidence: 95%
“…Several studies have demonstrated a reduction in measured sputum viscosity as early as 4 days after treatment initiation (Edwards et al 1976;Braga et al 1990). Braga et al examined the sputum viscosity and elasticity of 53 patients with chronic bronchitis when treated with 4.5 g of carbocisteine daily for 5 days compared with placebo (Braga et al 1989).…”
Section: In Vitro Ex Vivo and In Vivo Properties Of Carbocisteine Mumentioning
confidence: 99%
“…Добавле-ние лизина к молекуле карбоцистеина (флуифорт) улуч-шает переносимость препарата, так как повышается его pH и, следовательно, минимизируются нежелательные явления со стороны желудочно-кишечного тракта. Флуи-форт обладает так называемым эффектом «последей-ствия», что подтверждает нормализация вязкости и эла-стичности секрета и мукоцилиарного транспорта в тече-ние 8 дней после 4-дневного курса терапии [5].…”
unclassified